Emphysematous pyelonephritis with rare and severe iliac vascular complications: a case report and review - Gao, Pan; Yang, Han; Zhang, Zhi (Frontiers in Medicine, 2025)
Emphysematous pyelonephritis (EPN) is a rare but severe necrotizing infection often associated with diabetes, ureteral obstruction, and gas production in the renal parenchyma and perinephric area. This report describes a 54-year-old man with type 2 diabetes who presented with right lumbar pain and was diagnosed with EPN complicated by right ureteral calculi and perinephric gas accumulation. Despite initial improvement with fluid resuscitation, antibiotics, and drainage, inadequate blood glucose control led to a worsening of the infection, eventually involving the psoas major muscle and iliac vessels. This progression resulted in the formation of an iliac aneurysm, which required endovascular surgery. The patient’s recovery was supported by proper blood glucose management and targeted antibiotic therapy. This case highlights the importance of early recognition, appropriate management, and strict glycemic control in preventing severe complications of EPN.